Discursive Governance in Politics, Policy, and the Public Sphere
XV, 235 p.
Keywords: This book studies the dynamics of political discourse in governance processes. It demonstrates the process in which political discourses become normative mechanisms, first marking socially constructed realities in politics, second playing a role in delineating the subsequent policy frames, and third influencing the public sphere.